The psycholinguistic factors of indirect translation in ukrainian literary and religious contexts - Kolomiyets, Lada; Коломієць, Лада (Lesya Ukrainka Eastern European National University, 2019)
The study of indirect translations (IT) into Ukrainian, viewed from a psycholinguistic perspective, will contribute to a better understanding of Soviet national policies and the post-Soviet linguistic and cultural condition. The paper pioneers a discussion of the strategies and types of IT via Russian in the domains of literature and religion. In many cases the corresponding Russian translation, which serves as a source text for the Ukrainian one, cannot be established with confidence, and the “sticking-out ears” of Russian mediation may only be monitored at the level of sentence structure, when Russian wording underlies the Ukrainian text and distorts its natural fluency. The discussion substantiates the strategies and singles out the types of IT, in particular, (1) Soviet lower-quality retranslations of the recent, and mostly high-quality, translations of literary classics, which deliberately imitated lexical, grammatical, and stylistic patterns of the Russian language (became massive in scope in the mid1930s); (2) the translationfrom-crib type, or translations via the Russian interlinear version, which have been especially common in poetry after WWII, from the languages of the USSR nationalities and the socialist camp countries; (3) overt relayed translations, based on the published and intended for the audience Russian translations that can be clearly defined as the source texts for the IT into Ukrainian; this phenomenon may be best illustrated with Patriarch Filaret Version of the Holy Scripture, translated from the Russian Synodal Bible (the translation started in the early 1970s); and, finally, (4) later Soviet (from the mid1950s) and post-Soviet (during Independence period) hidden relayed translations of literary works, which have been declared as direct ones but in fact appeared in print shortly after the publication of the respective works in Russian translation and mirrored Russian lexical and stylistic patterns.Дослідження опосередкованих перекладів українською мовою з перспективи психолінгвістики допоможе глибше збагнути радянську національну політику та пострадянську мовно-культурну ситуацію. У статті вперше встановлюються й цілісно окреслюються стратегії та типи перекладів, опосередкованих російською мовою, в галузях літератури і релігії. У багатьох випадках неможливо однозначно вказати на відповідні російські переклади, які виступають джерелом для українських текстів, і лише на синтаксичному рівні вдається простежити як крізь українські слова прозирають російські тексти, які руйнують природний плин української мови. Авторка обґрунтовує стратегії та окреслює типи опосередкованого перекладу, зокрема 1) радянські повторні переклади нижчої якості, ніж нещодавно зроблені якісні переклади класичних творів, які зумисно імітують лексичні, граматичні та стилістичні зразки російської мови (цей тип набув масового характеру з середини 1930-х років); 2) переклад-зі-шпаргалки, тобто переклади через російські підрядники, які були особливо поширеними в жанрі поезії після другої світової війни; 3) відкриті естафетні переклади, які спираються на опубліковані для російської аудиторії російськомовні переклади, що їх можна легко ідентифікувати як джерельні тексти для опосередкованих українських перекладів; найкраще це явище вдалося проілюструвати перекладами Святого Письма, зробленими Патріархом Філаретом з російської синодальної Біблії (цю справу було розпочато ще на початку 1970-х років); нарешті, 4) пізньорадянські (з середини 1950-х років) та пострадянські (протягом періоду незалежності) приховані естафетні переклади художніх творів, про які видавці заявляють як про прямі переклади, але їхня фактична поява відразу після публікації відповідних творів російською мовою та лексико-стилістична схожіть на російські відповідники свідчить про їхню опосередкованість.
Психолінгвістичні фактори опосередкованого перекладу в українському літературному та релігійному контекстах
Keywords: psycholinguistic factors; strategies and types of translation; indirect translation; retranslation; translation-from-crib; relayed translation; intermediary language; психолінгвістичні фактори; стратегії та типи перекладу; опосередкований переклад; повторний переклад; переклад-зі-шпаргалки; естафетний переклад; мова-посередник